Leveraging Digital Ecosystems for Strategic Growth in B2B IT Startups : A Case Study of Buinsoft - Basko, Polina; Ali, Tanweer; Ng, Chia Hui; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2025)
This bachelor thesis examines how digital ecosystems contribute to the strategic growth of B2B IT startups, using Buinsoft as a case study. The main objective was to explore how ecosystem participation enables scalability, innovation, operational efficiency, and market access as drivers of growth. A qualitative methodology was applied, including a semi-structured interview with the CEO, review of internal company materials, ecosystem mapping, SWOT analysis and importance ranking tools. The research identifies key benefits such as flexibility, faster development, cost-effectiveness, and improved client engagement. However, challenges such as platform dependency, unexpected costs, and data privacy risks were also identified. The thesis concludes that digital ecosystems can significantly support startup growth if selected and managed strategically.
Vedoucí práce: Tanweer Ali
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: bachelor of business administration [obor bakal. práce]; bakalářské práce; bachelor's theses